British Association for Sexual Health and HIV national guideline for the management of Genital Molluscum in adults (2021). (April 2022) - Fernando, Imali; K Edwards, Sarah; Grover, Deepa
This guideline offers recommendations on diagnosis, treatment regimens and health promotion principles needed for the effective management of genital molluscum, including management of the initial presentation and recurrences. The Primary focus of the guideline is on infection which affects the genital area and has a sexual mode of transmission. This is an update to the guideline previously published in this journal in 2014.